Tissue-specific localization of polyketide synthase and other associated genes in the lichen, Cladonia rangiferina, using laser microdissection. (December 2018) - Elshobary, Mostafa E.; Becker, Michael G.; Kalichuk, Jenna L.; Chan, Ainsley C.; Belmonte, Mark F.; Piercey-Normore, Michele D.
Abstract: The biosynthesis of two polyketides, atranorin and fumarprotocetraric acid, produced from a lichen-forming fungus, Cladonia rangiferina (L.) F. H. Wigg. was correlated with the expression of eight fungal genes ( CrPKS1, CrPKS3, CrPKS16, Catalase ( CAT ), Sugar Transporter ( MFsug ), Dioxygenase ( YQE1 ), C2 H2 Transcription factor ( C 2 H 2 ), Transcription Factor PacC ( PacC ), which are thought to be involved in polyketide biosynthesis, and one algal gene, NAD-dependent deacetylase sirtuin 2 (AsNAD)), using laser microdissection (LMD). The differential gene expression levels within the thallus tissue layers demonstrate that the most active region for potential polyketide biosynthesis within the lichen is the outer apical region proximal to the photobiont but some expression also occurs in reproductive tissue. This is the first study using laser microdissection to explore gene expression of these nine genes and their location of expression; it provides a proof-of-concept for future experiments exploring tissue-specific gene expression within lichens; and it highlights the utility of LMD for use in lichen systems. Graphical abstract: Image 1 Highlights: The most active region for PKS gene expression is the outer thallus tissue near the photobiont. PKS gene expression is active in the reproduction structures. The outer thallus tissue is more active in PKS-associated gene expression, with two exceptions.